1998
DOI: 10.1159/000014026
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age-Dependent Reference Values for Iron and Selected Proteins of Iron Metabolism in Serum of Premature Human Neonates

Abstract: The diagnosis and treatment of fetal and neonatal diseases requires knowledge of gestational age-dependent reference ranges for most laboratory values. It was the aim of the present study to establish reference values for serum iron, transferrin, ferritin and ceruloplasmin concentrations in premature neonates, thereby paying attention to the possible changes with gestational age. Blood samples were taken from 100 premature neonates within the first hour of life. Total serum iron, transferrin, ferritin and ceru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 16 publications
1
22
0
3
Order By: Relevance
“…The transfused adult haemoglobin increases oxygen delivery to the retina which may increase the risk of ROP 23 . Lackman 24 in his study has demonstrated that increased amount of free iron may catalyze fenton reactions, which produce free hydroxyl radicals from superoxide and hydrogen peroxide capable of damaging the retina.…”
Section: Discussionmentioning
confidence: 99%
“…The transfused adult haemoglobin increases oxygen delivery to the retina which may increase the risk of ROP 23 . Lackman 24 in his study has demonstrated that increased amount of free iron may catalyze fenton reactions, which produce free hydroxyl radicals from superoxide and hydrogen peroxide capable of damaging the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Measures used to evaluate iron status in adults and children are not useful in neonates because of developmental changes that occur over the first 6 months of life. [9][10][11] Specific bone marrow staining is a reliable index of iron status, but it is not practical for serial assessment of iron status in the premature infant.…”
mentioning
confidence: 99%
“…Nas células placentárias, ocorre a liberação do ferro e o retorno da apoproteína para a circulação materna. 5,9 A incorporação de ferro pelo feto é proporcional ao seu peso corporal. Como o mais importante aumento de peso fetal ocorre no último trimestre da vida intrauterina, a criança prematura e a que sofreu retardo de crescimento intrauterino, resultando num baixo peso ao nascer, acumularão menos ferro em comparação ao recém-nascido a termo e de peso adequado para a idade gestacional.…”
Section: O Sistema Hematopoético Do Fetounclassified
“…A ferritina se altera frente a processos inflamatórios, dificultando a interpretação real do status do ferro no organismo. Durante o período neonatal, consideramos valores de ferritina abaixo de 100 ng/mL 9,25 indicativos de deficiência de ferro, sendo indicada a utilização de doses terapêu-ticas de reposição de ferro.…”
Section: Avaliação Laboratorialunclassified